Integrating nutriepigenomics in Parkinson's disease management: new promising strategy in the omics era - Razali, Khairiah; Algantri, Khaled; Loh, Su Peng; Cheng, Shi Hui; Wael Mohamed (Elsevier, 2022)
Parkinson’s disease (PD) is the most prevalent brain motor disorder and is frequently regarded as an idiopathic and sporadic disease due to its unclear etiology. Although the pathological mechanisms of PD have already been investigated at various omics levels, no disease-modifying drugs are currently available. At the moment, treatments can only provide symptomatic relief to control or improve motor symptoms. Parkinson’s disease is a multifactorial disease, the development and progression of which are influenced by multiple factors, including the genetic markups and the environment. As an indispensable component of our daily life, nutrition is considered one of the most robust environmental factors affecting our health. Consequently, depending on our dietary habits, nutrition can either induce or reduce our susceptibility to PD. Epigenetic mechanisms regulate gene expression through DNA methylation, histone modifications, and non-coding RNAs (ncRNAs) activity. Accumulating evidence from nutriepigenomics studies has reported altered epigenetic mechanisms in clinical and pre-clinical PD models, and the potential role of nutrition in modifying the changes. In addition, through nutrigenetics and nutrigenomics studies, the diet-gene, and gene-diet interactions concerning PD development and progression have been investigated. Herein, current findings on the roles of nutrition in epigenetic mechanisms underpinning PD development and progression are discussed. Recent advancements in the multi-omics approach in PD nutrition research are also underlined. The ability of nutrients to influence epigenetic mechanisms and the availability of multi-omics applications compel the immediate use of personalized nutrition as adjuvant therapy for PD.